Cocaine and amphetamine addiction genetics - Breen, Gerome (Henry Stewart Talks, 2007)
Heritability of cocaine and other addictions, Gene-environment interactions and addiction, The Dopamine transporter gene (SLC6A3), Brazilian Cocaine Association sample, Case-control cohort from Sao Paulo, Brazil, Association between the variants and cocaine addiction, Potential study confounders, Correcting for population stratification, Reporter-gene assays indicating that the VNTR is a differential response element, Functional assay of associated genetic variation, Different expression levels of the alleles, Allele and genotype association between DAT-intron 8 VNTR and cocaine, Similar studies on amphetamine and methamphetamine addiction